ANAK ANGKAT DI PERSIMPANGAN HUKUM - M. Fahmi Al Amruzi (Masalah-Masalah Hukum, 2014)
History records that the adopted child and the adoption has been known for a long time ago. This adoption can occur due to personal and social interests, such as not having children because of infertility or other reasons, or aimed to assist and uplift the community as a result of the economic downturn. Legal adoption both in Arabia as well as other places such as China and even in Indonesia has a long history, and even in the Arab lands once canceled, While in the prevailed Ducth Colonial law period to Indonesia, no law of adoption.